Anaesthetic management during intracranial mechanical thrombectomy: systematic review and meta-analysis of current data. Issue 1 (26th September 2018) - Gravel, Guillaume; Boulouis, Grégoire; Benhassen, Wagih; Rodriguez-Regent, Christine; Trystram, Denis; Edjlali-Goujon, Myriam; Meder, Jean-François; Oppenheim, Catherine; Bracard, Serge; Brinjikji, Waleed; Naggara, Olivier N
Abstract : Objective: Our aim was to compare the clinical outcome of patients with ischaemic stroke with anterior large vessel occlusion treated with stent retrievers and/or contact aspiration mechanical thrombectomy (MT) under general anaesthesia (GA) or conscious sedation non-GA through a systematic review and meta-analysis. Methods: The literature was searched using PubMed, Embase and Cochrane databases to identify studies reporting on anaesthesia and MT. Using fixed or random weighted effect, we evaluated the following outcomes: 3-month mortality, modified Rankin Score (mRs) 0–2, recanalisation success (thrombolysis in cerebral infarction (TICI) ≥2b) and symptomatic intracerebral haemorrhagic (sICH) transformation. Results: We identified seven cohorts (including three dedicated randomised controlled trials), totalling 1929 patients (932 with GA). Over the entire sample, mortality, mRs 0–2, TICI≥2b and sICH rates were, respectively 17.5% (99% CI 9.7% to 29.6%; Q-value: 60.1; I 2 : 93%, 1717 patients), 42.1% (99% CI 33.3% to 51.7%; Q-value: 41.3; I 2 : 87.9%), 82.9% (99% CI 74.0% to 89.1%; Q-value: 20.7; I 2 : 80.6%, 1006 patients) and 5.5% (99% CI 2.8% to 10.8%; Q-value: 18.6; I 2 : 78.5%). MT performed in non-GA patients was associated with better 3-month functional outcome (pooled OR, 1.35; 99% CI 1.04 to 1.76; Q-value: 24.0; I 2 : 9.2%, 1845 patients) and lower 3-month mortality rate (pooled OR, 0.70; 99% CI 0.49 to 0.98; Q-value: 1.4; I 2 : 0%, 1717 patients; fixed weighted effect model) compared with GA. MT performed under conscious sedation non-GA had significantly shorter onset-to-recanalisation and onset-to-groin delay compared with GA, and recanalisation success and sICH were similar. Conclusion: Non-GA during MT for anterior acute ischaemic stroke with current-generation stent retriever/aspiration devices is associated with better 3-month functional outcome and lower mortality rates. These unadjusted estimates are subject to biases and should be interpreted with caution.